Introduction: Transnational gender cultures and reality TV. (February 2017) - Kavka, Misha; Weber, Brenda R
Having gained a global foothold in popular culture, reality TV offers to explicate, regulate and manipulate the social scripts we live by. This issue makes the claim that a transnational approach to reality TV provides a rich context for interrogating the international variability of gender cultures. As the analyses that are presented in this Special Issue indicate, while gender formations may operate according to globally patriarchal scripts, the manifestations, manipulations and resistances to such a script take locally specific forms, as shaped by the social, political and industrial histories of each particular place but with broader bearing on more 'worldwide' concerns, such as hegemony, patriarchy and capital.